Transitional constitutionalism in the United Kingdom - McLean, I; Peterson, S (Edward Elgar Publishing, 2014)
The UK's transitional constitution dates to 1707, when two conceptions of constitutionalism—parliamentary sovereignty and popular sovereignty—were bound together under a single government of Great Britain. Three members of one family, John MacDonald MacCormick, Professor Sir Neil MacCormick and Iain MacCormick, were instrumental in creating an environment in which it continues to change in the present day. The constitution that was proposed for Scotland in the context of the 2014 referendum included positive elements that may influence the development of the constitution of the UK, now that Scotland has chosen, at least for the short term, to remain in the union.